2004
DOI: 10.1097/00008506-200410000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intraocular Pressure in Anesthetized Prone Patients

Abstract: IOP increases when anesthetized patients are placed in the prone position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 29 publications
6
52
1
3
Order By: Relevance
“…These fi ndings are in accordance with previous studies 8,9 . Our results have also suggested that when patients were positioned prone with their heads rotated 45 o laterally, IOP in the upper positioned eyes were signifi cantly lower than lower positioned eyes and IOP of the patients positioned prone without head rotation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These fi ndings are in accordance with previous studies 8,9 . Our results have also suggested that when patients were positioned prone with their heads rotated 45 o laterally, IOP in the upper positioned eyes were signifi cantly lower than lower positioned eyes and IOP of the patients positioned prone without head rotation.…”
Section: Discussionsupporting
confidence: 94%
“…Since ocular perfusion pressure is commonly defi ned as the difference between mean arterial pressure (MAP) and IOP, the authors drew attention to the fact that ocular perfusion pressure could decrease despite maintenance of normotension during surgery in prone position 8 . In a similar study, Hunt et al 9 also studied patients undergoing spinal surgery and found that IOP increased when anesthetized patients are placed in prone position. Those in prone positions were signifi cantly higher than supine positions.…”
Section: Discussionmentioning
confidence: 94%
“…It is reported that patients who have undergone spinal surgery in the prone position showed elevated IOP during anesthesia [25,26]. Because all patients in our study were kept in the prone position after surgery, it could have had an influence on their postoperative IOP.…”
Section: Resultsmentioning
confidence: 89%
“…-Obwohl bekannt ist, dass der intraokuläre Druck in BauchIagerung erhöht ist [19], gibt es bislang keine Daten zum Einfluss der Flexion bzw. orthograden oder Seitlagerung des Kopfes in Bauchlagerung auf den intraokulären Druck.…”
Section: Gibt Es Präventivmaßnahmen?unclassified
“…Demzufolge sind gerade Glaukompatienten gefähr-det, eine ischämische N.-opticus-Neuropathie zu erleiden [54]. Zudem wird der intra okuläre Druck durch eine Bauchlagerung erhöht [19]. [31].…”
Section: Introductionunclassified